2008
DOI: 10.1111/j.1468-1331.2007.02052.x
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 Gly2385Arg variant is a risk factor of Parkinson’s disease among Han‐Chinese from mainland China

Abstract: Mutations in the gene encoding Leucine-rich repeat kinase 2 (LRRK2) have been recently linked with autosomal-dominant parkinsonism, and polymorphisms have been commonly associated with sporadic Parkinson's disease (PD). A p.2385G>R variant has been reported as a risk factor for PD in Taiwan, Singapore and Japan. Herein, we have assessed the frequency of this polymorphism among the ethnic Han-Chinese population in a case-control study. A total of 600 patients with PD and 334 unrelated healthy controls were geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 30 publications
4
48
2
1
Order By: Relevance
“…1 FTLD is the second most common cause of presenile dementia after Alzheimer's disease (AD) [1][2][3] and accounts for 5 to 10% of neurodegenerative dementias in epidemiological samples and between 9 and 16% in autopsy series. 1 Clinical subtypes of FTLD include (1) a behavioral variant with predominant frontotemporal involvement, (2) semantic dementia, and (3) primary progressive aphasia.…”
Section: Ann Neurol 2008;64:92-96mentioning
confidence: 99%
“…1 FTLD is the second most common cause of presenile dementia after Alzheimer's disease (AD) [1][2][3] and accounts for 5 to 10% of neurodegenerative dementias in epidemiological samples and between 9 and 16% in autopsy series. 1 Clinical subtypes of FTLD include (1) a behavioral variant with predominant frontotemporal involvement, (2) semantic dementia, and (3) primary progressive aphasia.…”
Section: Ann Neurol 2008;64:92-96mentioning
confidence: 99%
“…This work led to our initial identification of the association of Gly2385Arg with PD, a finding that has been rapidly and consistently replicated in Chinese populations from Singapore [5], Taiwan [6,7], mainland China [8,9], and in the Japanese population [10].…”
Section: Introductionmentioning
confidence: 99%
“…16,17,[34][35][36][37][38][39] One of these studies included 26 patients with a familial history of PD, among which six patients were p.G2385R carriers. 40 A meta-analysis on the basis of these studies involving 2205 PD patients and 1817 controls demonstrated average carrier rates of 9.3% in PD and 4% in controls.…”
Section: Discussionmentioning
confidence: 99%